Romania's foreign debt crisis in the 1980s: Determinants and consequences - George Georgescu (Romanian Academy, National Institute for Economic Research, 2018)
Based on more recent research and evidence, including declassified information regarding the communist period in Romania, the study focuses on examining the 1980s foreign debt crisis context, its determinants and consequences, the impact of internal and external factors, intending to provide an image closer to reality of this dramatic episode. The global economy faced a severe economic and financial crisis at the beginning of the 1980s, when more than 30 developing countries entered default or restructuring on the sovereign debt. In the case of Romania, the impact of the foreign debt crisis triggered in 1981-1982 proved to be extremely hard, worsened by the overlap between the internal vulnerabilities accumulated in previous decades and the external shock coming from the major changes in the global economic, financial and geopolitical context at the end of 1979. The FED monetary policy at that time has led to the explosive rise in interest rates of the outstanding loans contracted from international commercial banks, to which Romania was highly indebted. The decision of simple-minded Ceausescu to liquidate the foreign debt and other serious errors concerning the crisis management had a destructive impact on the Romanian economy, which degenerated in a system crisis ended with its implosion in December 1989. Some consequences of the foreign debt crisis were felt also afterwards, slowing down significantly the pace of Romania's transition to the market economy.
Keywords: B22; E44; E62; F34; H63; N44; 330; foreign debt crisis; oil crisis shocks; IMF; FED monetary policy; interest rates; sovereign debt restructuring; Romania